2016
DOI: 10.21767/2172-0479.100059
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Duct Opening into Right Hepatic Duct; a Disaster Waiting to Happen During Cholecystectomy: A Case Report

Abstract: Cholecystectomy is the most commonly performed elective surgery worldwide. Variations in the normal anatomy of the biliary tree are common. Cystic duct variations are surgically most significant. Incidence of cystic duct opening into right hepatic duct is very low. In the case presented in this report cystic duct opened into the right hepatic duct. An abnormally wide cystic duct made us suspicious and after careful dissection we could trace the cystic duct entering into right hepatic duct. Various radiologic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…A single (2%) study participant had the cystic duct drained through the right hepatic duct. This corresponds to the findings of previous studies who found that cystic duct may join the right hepatic duct in 0.6%-2.3% cases (17,18).…”
Section: Cystic Ductssupporting
confidence: 92%
See 1 more Smart Citation
“…A single (2%) study participant had the cystic duct drained through the right hepatic duct. This corresponds to the findings of previous studies who found that cystic duct may join the right hepatic duct in 0.6%-2.3% cases (17,18).…”
Section: Cystic Ductssupporting
confidence: 92%
“…These findings compare to an American study which found that the cystic duct enters the extrahepatic bile duct from the right lateral aspect in 49.9% of cases, from the medial aspect (left) in 18.4%, and from an anterior or posterior position in 31.7% (16). An Indian study found a medial (left) insertion in 10%-17% (17). A single (2%) study participant had the cystic duct drained through the right hepatic duct.…”
Section: Discussionmentioning
confidence: 99%
“…This fi nding is compatable with a case study done in Brazil. The right hepatic duct may be mistakenly ligated and severed being considered as a cystic duct and may lead to severe complications in patient 18 . Another variation called apparent common bile duct was observed in 6 (1.36%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…(7) The double cystic duct opening into the right hepatic duct has been observed in 1 dissection, that of a female cadaveric specimen(Fig- 9) .This condition is very rare with very few cases reported in world literature. (18,19,20) Double cystic duct i.e. one draining into the RHD and one to the CHD has been observed in 1 dissection (1%) in a specimen belonging to a male cadaver.…”
Section: Discussionmentioning
confidence: 99%